2014
DOI: 10.12691/ajmbr-2-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Pattern of Endoscopic Gastric Biopsy in a District Hospital in Nigeria: A Review of 118 Consecutive Cases

Abstract: Background: The use of endoscopes for visualization of gastric mucosa has improved over times and in taking biopsy for histology. The study sets out to determine the histopathological pattern of gastritis in dyspeptic patients and correlate the histological detection of H. pylori with that of urease breath test (UBT). Method: Prospective study of 118 consecutive patients with chronic dyspepsia who underwent upper gastrointestinal endoscopic examination and UBT using heliprobe. Biopsy of gastric antrum were tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…2 Study conducted in India shown 6.2%, 84% and 2.6% proportions for disorders of oesophagus, stomach and duodenum, 5.6% patients had unremarkable histologically and one patients was inadequate for opinion. 4 The gastritis 76% reported to being the most common inflammatory lesion on histopathological evaluation. 5 Other lesions diagnosed were non-specific as Barrett oesophagus 1.5%, oesophagitis 1.54%, gastric ulcer 3.5%, GERD 1.7%, and duodenitis 3.1%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Study conducted in India shown 6.2%, 84% and 2.6% proportions for disorders of oesophagus, stomach and duodenum, 5.6% patients had unremarkable histologically and one patients was inadequate for opinion. 4 The gastritis 76% reported to being the most common inflammatory lesion on histopathological evaluation. 5 Other lesions diagnosed were non-specific as Barrett oesophagus 1.5%, oesophagitis 1.54%, gastric ulcer 3.5%, GERD 1.7%, and duodenitis 3.1%.…”
Section: Introductionmentioning
confidence: 99%
“…2 The endoscopy performed for diagnosis as well as determining the extension of the disease, monitoring treatment course, treatment response and detection of early complications. [4][5][6] In this regard the indications of biopsy expands and covers wide range of pathological conditions. 7,8 Majority of the individuals had clinical suspicious for GERD or GI discomfort but endoscopic findings are unremarkable and non specific and labeled as endoscopic negative GERD.…”
Section: Introductionmentioning
confidence: 99%
“…4,8,10,11,17,18,20,21 Nigeria and Africa.The reported range Dyspepsia affectation in this study did not show a sex predilection as demonstrated by a male to Discussion associated gastritis, 7(5.8%) cases of chronic non H. Pylori associated gastritis, 9 (7.5%) cases of chronic non H. Pylori associated gastritis with metaplasia, 6 (5%) cases of chronic non H. Pylori associated gastritis with atrophy and metaplasia, 2 (1.7%) cases of chronic non H. Pylori associated gastritis with ulcer, dysplasia and metaplasia. In addition, there were also 13 (10.8%) cases of chemical gastritis with erosion and ulceration, 4 (3.3%) cases of adenocarcinoma, 3 (2.5%) cases of polyps, while 17(14.2%) of the cases were essentially normal gastric tissues (table1).www.ibommedicaljournal.org 5.…”
mentioning
confidence: 99%